The influence of company size, company growth, and profitability on company value with capital structure as a moderating variable in the 10 largest conventional banks in Indonesia 2017-2022 - Panjaitan, Florensy; Sari, Agustin Rusiana (Institute of Accounting Research and Novation (IARN), 2024)
This research aims to analyze the influence of company size, company growth and company profitability on company value with capital structure as a moderating variable. The companies that are the object of research are the 10 Conventional Banks with the Largest Assets according to the OJK 2017-2022. The type of data used in this research is quantitative data. The data source used in this research is secondary data taken from the Indonesia Stock Exchange at 10 Conventional Banks. The relationship or influence of these variables is explained using the multiple regression analysis method. The data used in this research used 60 samples. The test tool used is SPSS 25. The results of the research show that Company Size has an effect on Company Value, Company Growth has an effect on Company Value, Company Profitability has no effect on Company Value, Capital Structure does not moderate the effect of Company Size. on company value, capital structure is not able to moderate the effect of company growth on company value, capital structure is not able to moderate the effect of company profitability on company value.